The Effects of Credit Rating Announcements on Stock Return in Malaysia - Husin, Norsuhaida (2010)
This study aims to provide a comprehensives investigation of the effect of bond rating changes on stock returns in Malaysia between the years 2000-2008. The study examines the rating changes of both Private Debt Securities (PDS) and Islamic Private Debt Securities (IPDS) based on ratings by RAM Rating Services Berhad (RAM) and Malaysia Rating Corporation Berhad (MARC). All the data are collected from RAM, MARC, Bond Pricing Agency Malaysia, Thomson Datastream, Securities Commission and Bank Negara Malaysia. The abnormal returns are calculated by using event study methodology and the beta is adjusted by using Dimson-Fowler Rorke (DFR) method. The findings reveal that when there is an announcement of rating upgrades for PDS, stock price react negatively and affect the firm returns while for IPDS the effect is negative but insignificant. The results for downgrades of PDS show that stock market responds negatively and significant while for IPDS it is negative but insignificant. This study also identifies determinants of abnormal return on bond announcement with associated firm (FIRM SIZE & LEVERAGE) and bond-specific factors (MATURITY).There is useful information for PDS and IPDS on the LEVERAGE of the rating change.